Conjecture of operational parameters in the removal of apparent color and turbidity of a textile effluent by adsorption technology - Almeida, Maria Eduarda Borges de; Pequeno, Lucas Alves Batista; Carvalho, Marilda Nascimento; Tavares, Rosângela Gomes (Journal of Environmental Analysis and Progress, 2023)
Creating a sustainable textile industry involves correctly disposing of production waste. The treatment by adsorption for effluents containing high levels of dyes is widely used compared to other conventional methods. Activated carbon is the adsorbent that receives more attention due to its high capacity to capture molecules by chemical interaction. Among the various factors that can influence adsorption, pH is very important because it determines the electrostatic interactions between the adsorbate and the adsorbent. In this context, it is necessary to know the pH at which the charge balance is null on the surface of the solid, that is, the point of zero charge (PZC). Therefore, the purpose of this study was to determine the PZC of the activated carbon, by the "11 points experiment" method, and to evaluate the efficiency of the adsorption technique for treating a textile effluent. The parameters of apparent color and turbidity were used as response variables. Thus, the best pH range activated carbon dosage, and shaking time for the treatment were defined. The conjecture of the ideal amount of adsorbent it was observed as the best result with the concentration of 5 g/L, which reached a maximum removal of 91.22% and 91.04% in shaking time of 20 min, for turbidity and apparent color, respectively.